Odpowiedzi

2009-11-25T14:50:29+01:00
13x-8(3x-2)=-7x-5(12-3x)
13x-24x+16=-7x-60+15x
-11x+16=8x-60
-19x=-76 /19
x=4

7(2x-1)-6(11-x)=3(x+4)
14x-7-66+6x=3x+12
20x-73=3x+12
17x=-85 /17
x=-5

(x+5)(x+2)-3(4x-3)=(x-5)²
x²+2x+5x+4-12x+9=x²+25-10x
-5x+13=-10x+25
5x=12 /5

12-2(x-1)²=4(x-2)-(x-3)(2x-5)
12-2(x²+1-2x)=4x-8-(2x²-5x-6x+15)
12-2x²-2+4x=4x-8-2x²+5x+6x-15
4x+10=15x-23
-11x=-33 /-11
x=3
x=2 i 2/5
2009-11-25T14:52:25+01:00
A)13x-8(3x-2)=-7x-5(12-3x)
13x-24x+16=-7x-60+15x
13x-24x+7x-15x=-60-16
-19x=-76 /:(-19)
x=4
B)7(2x-1)-6(11-x)=3(x+4)
14x-7-66+6x=3x+12
14x+6x-3x=12+66+7
17x=85 /:(17)
x=5
C)(x+5)(x+2)-3(4x-3)=(x-5)²
x²+2x+5x+10-12x+9=x²-5²
x²+2x+5x-12x-x²=25-9-10
-5x=6 /:(-5)
x=-1.2
D)12-2(x-1)²=4(x-2)-(x-3)(2x-5)
12-2(x²-1²)=4x-8-(2x²-5x-6x+15)
12-2x²+2=4x-8-2x²+5x+6x-15
-2x²-4x+2x²-5x-6x=-15-8-2-12
-15x=-43
x=2,8666.....